2018
DOI: 10.1159/000486323
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ultrafiltration Rate with Mortality in Incident Hemodialysis Patients

Abstract: Background/Aims: Ultrafiltration rate (UFR) appears to be associated with mortality in prevalent hemodialysis (HD) patients. However, the association of UFR with mortality in incident HD patients remains unknown. Methods: We examined a US cohort of 110,880 patients who initiated HD from 2007 to 2011. Baseline UFR was divided into 5 groups (<4, 4 to <6, 6 to <8, 8 to <10, and ≥10 mL/h/kg body weight [BW]). We examined predictors of higher baseline UFR using logistic regression and the association of baseline UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
6
20
1
Order By: Relevance
“…Among critically ill patients receiving CVVHDF, we found that an NUF rate greater than 1.75 mL/kg/h compared with an NUF rate less than 1.01 mL/kg/h was associated with lower risk-adjusted 90-day survival between day 7 and day 90. These findings are aligned with several recent studies in outpatients with end-stage renal disease 10 , 11 , 12 , 13 that found that higher NUF rates are associated with decreased survival.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among critically ill patients receiving CVVHDF, we found that an NUF rate greater than 1.75 mL/kg/h compared with an NUF rate less than 1.01 mL/kg/h was associated with lower risk-adjusted 90-day survival between day 7 and day 90. These findings are aligned with several recent studies in outpatients with end-stage renal disease 10 , 11 , 12 , 13 that found that higher NUF rates are associated with decreased survival.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, emerging evidence from outpatients with end-stage renal disease receiving hemodialysis suggests that an NUF rate greater than 13 mL/kg/h per session compared with an NUF rate of 10 mL/kg/h or less is associated with mortality. 10 , 11 , 12 , 13 However, the implications and generalizability of these study findings to patients undergoing continuous NUF are unclear.…”
Section: Introductionmentioning
confidence: 86%
“…It remains to be investigated whether the reduction of recovery time may be obtained with the increase of the UFR in the routine clinical practice and whether this is appropriate. In fact, it is well known that a higher UFR has been associated with increased mortality [19][20][21] and with hemodynamic effects such as reduced myocardial blood and myocardial stunning [22][23][24]. Nevertheless, an ideal UFR has not yet been identified [25].…”
Section: Discussionmentioning
confidence: 99%
“…Various risk factors for worse survival rates have been reported [3][4][5][6][7][8][9]. High ultrafiltration rate (UFR), that is, rapid fluid removal, is recognized as one of the risk factors responsible for these poor outcomes [10][11][12][13][14]. High UFR could increase the development of intradialytic hypotension (IDH), which might be associated with end-organ ischemia of the heart, brain, DOI: 10.1159/000509350 and gut, and this may consequently lead to increased mortality risk [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%